Neuropathologic Findings in Elderly HIV-Positive Individuals. Issue 7 (3rd June 2022) - Magaki, Shino D; Vinters, Harry V; Williams, Christopher K; Mareninov, Sergey; Khanlou, Negar; Said, Jonathan; Nemanim, Natasha; Gonzalez, Jessica; Morales, Jose G; Singer, Elyse J; Yong, William H
Abstract: The elderly HIV-positive population is growing due to the widespread use of combination antiretroviral therapy (cART), but the effects of longstanding HIV infection on brain aging are unknown. A significant proportion of HIV-positive individuals develop HIV-associated neurocognitive disorder (HAND) even on cART, but the pathogenesis of HAND is unknown. Although neuroinflammation is postulated to play an important role in aging and neurodegenerative diseases such as Alzheimer disease (AD), it is unclear whether HIV accelerates aging or increases the risk for AD. We examined the brains of 9 elderly HIV-positive subjects on cART without co-infection by hepatitis C virus compared to 7 elderly HIV-negative subjects. Microglial and astrocyte activation and AD pathologic change in association with systemic comorbidities and neurocognitive assessment were evaluated. There was no difference in microglial or astrocyte activation between our HIV-positive and HIV-negative cohorts. One HIV-positive subject and 2 HIV-negative subjects demonstrated significant amyloid deposition, predominantly in the form of diffuse senile plaques, but these individuals were cognitively normal. Neurofibrillary tangles were sparse in the HIV-positive cohort. There was a high prevalence of cardiovascular comorbidities in all subjects. These findings suggest that multiple factors likely contribute to aging and cognitive impairment in elderly HIV-positive individuals on cART.